Strategi Customer Relations dan Kekayaan Media PT Mandiri Cipta Sejahtera Pada Masa Pandemi COVID-19 - Susilowati Susilowati; Titi Widaningsih; Toto Soebandoro (Jurnal Komunikasi, 2021)
The impact that occurred during the COVID-19 pandemic with the determination to work from home (WFH) which resulted in the obstruction of face-to-face communication activities with customers, thus requiring a strategy to establish relationships and maintain good communication with customers. The purpose of this study is to identify and describe the strategy of customer relations and the use of video conferencing using Zoom Cloud Meeting. The concept of Customer Relations Strategy used is Qutlip and Wood and Smith's Computer Mediated Communication (CMC) Theory and Daft and Lengel's Media Richness Theory. Research at PT Mandiri Cipta Sejahtera uses a qualitative approach with descriptive methods and uses the postpositivism paradigm. Data analysis uses Huberman and Miles data analysis, namely Data Reduction by collecting field data such as interviews, videos of the Zoom Meeting, data from the company's website and social media. The results of the study: (1) the company's customer strategy has met the stages of the customer relations strategy, namely; Fact Finding, Planning and programming, Taking action and communicating, evaluation, and the company has carried out customer relations activities, namely superior service to customers, excellent service (service off excellence) and good relations with customers (good relationship). (2) In the use of Zoom Cloud Meetings as a media resource, the implementation of Zoom Meetings is not fully media capable of sending many signals, and able to provide immediate feedback, can perform various languages, symbols and share data, also able to focus on delivering messages. Keywords: Strategi Customer Relations, Video Konfrensi,  Computer Mediated Communications, Kekayaan Media